RELEVANCE OF ACHARYA RAJNEESH’S EDUCATIONAL PHILOSOPHY IN THE CURRENT CONTEXT - Sidana, Ashok; Haldainiya, Hemant kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Acharya Rajneesh was a person who was seen seeking knowledge in everything since childhood. Acharya Rajneesh has given great importance to the freedom of the individual. Acharya Rajneesh’s philosophy is simple and unique. His thinking is different from other philosophers. He is known as an important philosopher not only in India but all over the world. In his philosophy, Acharya Rajneesh has presented his views on religion, politics, science, education, sex and women, Krishna, Kabir, Nanak and Mahatma Buddha. Acharya Rajneesh traveled all over India during his teaching period. Acharya Rajneesh was against socialism. He believed that the progress of India is possible only through capitalism, science, technology and reducing the birth rate. As a spiritual guru, he traveled from place to place and presented his views on various aspects. In a meditation camp organized for the public in 1970, Acharya Rajneesh first told about the “Dynamic Meditation Method”. Acharya Rajneesh revived “Samyak Sanyas” in his philosophy. In his view, a sannyasi is one who lives a life of meditation and satsang while fulfilling his familial and social obligations while living with his family, wife and children. Acharya Rajneesh gave new meaning to the mystics, philosophers and religious ideologies of the whole world in his teachings. He has shed light in detail on the mystics of various spiritual traditions like Yoga, Tantra, Zen, Hasid and Sufi. Along with this, his revolutionary life vision is also found on many subjects like politics, art, science, psychology, philosophy, education, family, society, poverty, population explosion, environment and possible nuclear war. In this article, the educational philosophy of Acharya Rajneesh sheds light on the inspiration of a conscious, self-conscious and blissful life.